Evaluating Potential Disease‐Mediated Protein‐Drug Interactions in Patients With Moderate‐to‐Severe Plaque Psoriasis Receiving Subcutaneous Guselkumab. Issue 6 (28th May 2020) - Zhu, Yaowei; Xu, Yan; Zhuang, Yanli; Piantone, Alexa; Shu, Cathye; Chen, Dion; Zhou, Honghui; Xu, Zhenhua; Sharma, Amarnath
Abstract : This open‐label, multicenter, phase I therapeutic protein‐drug interaction study was designed to evaluate the potential effect of guselkumab, a fully human anti‐interleukin‐23 immunoglobulin G1 lambda monoclonal antibody, on the pharmacokinetics of a cocktail of representative cytochrome P450 (CYP) probe substrates (midazolam (CYP3A4), S‐warfarin (CYP2C9), omeprazole (CYP2C19), dextromethorphan (CYP2D6), and caffeine (CYP1A2)). Fourteen participants with psoriasis received a single subcutaneous dose of guselkumab 200 mg on day 8 and an oral probe cocktail on days 1, 15, and 36. Blood samples were collected for measuring plasma concentrations of these probe substrates on days 1, 15, and 36. No consistent trends in observed maximum plasma concentration and area under the curve from time 0 to infinity values of each probe CYP‐substrate before (day 1) and after guselkumab treatment (days 15 and 36) could be identified in each individual patient, suggesting that the use of guselkumab in patients with psoriasis is unlikely to influence the systemic exposure of drugs metabolized by CYP isozymes (CYP3A4, CYP2C9, CYP2C19, CYP2D6, and CYP1A2). The probe cocktail was generally well‐tolerated when administered in combination with guselkumab in patients with psoriasis. Clinicaltrials.gov Identifiers: NCT02397382.